PENGARUH GAYA HIDUP HEDON, KUALITAS PRODUK, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN SEPEDA LISTRIK DI KOTA JUWANA - Mulyono, Fauzi; Haziroh, Awanis Linati; Wibowo, Mochammad Eric Suryakencana; Damar, Haunan (Universitas Nusa Cendana, 2024)
An electric bike, also known as an e-bike or power bike, could be a sort of bike that employs an electric motor as a control source. This thinks about points to get the relationship between hedonic style, product quality, and word of mouth on buying decisions of electric bikes. This investigation centers on individuals who purchase and utilize electric bikes in Juwana. The sampling technique is non-probability sampling. The data analysis utilized such as validity, reliability, normality, multicollinearity, heteroscedasticity, linear regression, and hypotheses test. The study found that hedonic lifestyle, product quality, and word of mouth influence buying decisions for electric bikes. Keywords: Hedonistic Lifestyle; Product Quality; Word of Mouth; Buying Decision